Study of the potential of nano hydroxyapatite in dental remineralization: An ex vivo study - Quandt, Daiane Vitória Duarte; do Nascimento, Luiza Helena Rocha; Coelho, Daniela Cunha; Garcia, Michele Cristina Formolo; da Silva, Daiara Floriana; Levandowski Junior, Nelson; Andrades, Kesly Mary Ribeiro (Seven Editora, 2023)
Introduction: Nanohydroxyapatite (nano-HAp) has been studied as a biomimetic material that promotes remineralization of the tooth surface and obliteration of dentinal tubules, being considered an alternative to the use of fluoride. In addition to the benefits to tooth structure and unlike fluoride, the accidental ingestion of nano-HAp as a component of toothpaste is not associated with any relevant systemic health risk. Objective: The aim of this study was to evaluate, in vitro, the potential of nano-HAp to remineralize the tooth structure, comparing three different formulations of toothpastes: pure synthetic nanohydroxyapatite, synthetic nanohydroxyapatite with fluoride and only fluoride, through electron microscopy scanning (SEM) and chemical analysis (EDS). Material and methods: A cross-sectional experimental study with a qualitative approach was carried out. Samples of teeth, third molars, cut into blocks, exposing enamel and dentin surfaces, were submitted to demineralization by immersion in 37% phosphoric acid for 30 seconds, followed by washing in running water. Subsequently, brushings were performed with the three toothpastes and in a control group, for 10 consecutive days. At the end of the experiment, a qualitative analysis was performed with Scanning Electron Microscopy (SEM) and chemical analysis (EDS). Results: It can be observed that in the control group there was no obliteration of the dentinal tubules and no change in the morphology of the dentin surface. In toothpastes with 5% nanohydroxyapatite and fluoride nanohydroxyapatite, mineral deposition on the dentin surface and obliteration of dentinal tubules can be observed, however, there is a more uniform deposition in toothpaste with 5% nanohydroxyapatite. In the fluoride toothpaste, it was possible to observe a mineral deposition, however, this was more subtle and only within some dentinal tubules, without altering the morphology of the dentin. Conclusion: It can be concluded that nanohydroxyapatite promoted a mineral deposition on the dentin surface and inside the dentinal tubules, demonstrating promising results in the remineralization of the tooth structure. DOI:https://doi.org/10.56238/interdiinovationscrese-001